(untitled) (International Journal of Research and Applied Technology (INJURATECH), 2023)
This research aims to provide an example or illustration of how to apply a simple accounting system, namely Microsoft Excel in a fashion business that has just been started and has not used an application or system to do the recording. This research used a literature study method. The results of this study are expected for business beginners, especially fashion businesses, to understand how recording and bookkeeping in accounting are created using a simple accounting application. By displaying steps on how to make general journals, ledgers, adjustment entries, profit, and loss in Microsoft Excel. Therefore, it can be concluded that how important it is to make recording and bookkeeping using a simple application system method so that it can be easily applied by fashion business people who have just entered the business field.